2017
DOI: 10.1108/jmd-06-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychological capital on organizational citizenship behavior

Abstract: Purpose The purpose of this paper is to examine the mediating role of work engagement (WE) between psychological capital (PsyCap) and the two facets of organizational citizenship behavior (OCB) which involves both individual and organization. It also examines the moderating role of perceived organizational support (POS) between PsyCap and WE, and WE and the two facets of OCB. Design/methodology/approach A total of 293 responses gathered from employees working in diverse service sector industries in India wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
129
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 31 publications
13
129
0
5
Order By: Relevance
“…The high level of job involvement is related to organizational citizenship behavior and work performance. The results of this study are in line with the results of research conducted by Manish Gupta (2017) who found that job involvement has a positive and significant effect on organizational citizenship behavior. Furthermore, research that is in line with this research is a study conducted by Andrew Adi Saputra (2013) who found results that work involvement has a positive and significant effect on organizational citizenship behavior.…”
Section: The Effect Of Job Involvement On Organizational Citizenship supporting
confidence: 91%
See 1 more Smart Citation
“…The high level of job involvement is related to organizational citizenship behavior and work performance. The results of this study are in line with the results of research conducted by Manish Gupta (2017) who found that job involvement has a positive and significant effect on organizational citizenship behavior. Furthermore, research that is in line with this research is a study conducted by Andrew Adi Saputra (2013) who found results that work involvement has a positive and significant effect on organizational citizenship behavior.…”
Section: The Effect Of Job Involvement On Organizational Citizenship supporting
confidence: 91%
“…This statement is supported by study conducted by Manish Gupta (2017) that results that work involvement is positively correlated on organizational citizenship behavior. It is in line with a study by Andrew Adi Saputra (2013) who finds that work involvement has significant and positive effect on organizational citizenship behavior.…”
Section: Introductionsupporting
confidence: 61%
“…Regarding the role of negative innovation outcomes as a mediator variable, it turns out that the negative innovation outcomes did not mediate the relationship between independent variables knowledge management and financial performance. This is supported by the results of Gupta and Acharya's (2018) research which states that there is no mediating effect of innovation between risk taking and performance. Considering that knowledge management did not significantly relate to SME financial performance, it is only risk taking that significantly and negatively related to negative innovation outcomes and positively related to financial performance.…”
Section: Discussionmentioning
confidence: 69%
“…This finding is encouraging for SMEs who are willing to take some risks. Risk taking is a result of thinking and acting in a different way (Gupta & Acharya, 2018). Perhaps, this is natural for these SMEs in creative industries.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between PsyCap and OCB was not direct; it was moderated or mediated by other variables. For example, Pradhan [3] found that PsyCap and OCB were moderated by Emotional Intelligence, while Gupta et al [22] discovered that the relationship was mediated by Work-Engagement. In terms of Nurses' performance, OCB also acts as desirable employee outcomes within the organization.…”
Section: Introductionmentioning
confidence: 99%